Symphonic style and structural tonality in the late eighteenth century with special emphasis on the music of Haydn - Parsonson, R (1980)
﻿ This thesis takes as its starting-point the theoretical and critical writings on music from the second half of the 18th century - mostly by German authors such as H.C. Koch and J.F. Daube. The intention is to illustrate the preoccupations and concepts of these authors in the period associated with the development of Classical symphonic style. I have noted the emphasis on textures and on certain aesthetic criteria, such as "Feuerigkeit" and "das Unerwartete", and I have attempted to trace the growth of meanings given to these terms over a period of about 50 years. To illustrate the formal implications of the "symphonic allegro" described in these writings, I have discussed specific examples in the second chapter from the symphonies of J.C. Bach, F.X. Richter, G. Pugnani, P. Beck, etc. (These are given in score in the Appendix of Musical Examples) Emphasis is placed on the contrasting roles of tutti and lightly-scored texture in articulating the internal structure of the first section of the allegro movement; and on the types of formal expansion (such as prolonged dominant preparation) and harmonic surprise already used by symphonic composers in the 1750s-60s. The third chapter is concerned exclusively with the symphonies of Haydn, illustrating his capacity to devise new relationships and roles for the traditional contrasts of texture and dynamic level in the symphonic allegro. The important sketch for the finale of Symphony No.99 is discussed, as a case in which the relationship between tutti transition and second subject is only gradually decided in the composer's plans. The harmonic aspects raised in connection with Haydn's symphonies are considered in more detail in the 4th chapter, which moves from the element of cadential expansion - in the form of interrupted cadences and interrupted or prolonged cadential progressions - to that of tonal contrasts at the level of independent and clearly defined periods which play a part in the thematic growth of the movement. The importance of flattened submediant and flattened mediant relationships are underlined in this context. Haydn's quartets have been largely used as the basis for this discussion. In the 5th chapter, the subject is the growing complexity and variety of tonal treatment in Haydn's development sections, from his observance of traditional key-schemes, through his experimentation with fausse reprise effects, to the enlargement of his procedures to include both flat and sharp key relationships. The chapter concludes with a discussion of the "enharmonic" modulatory schemes characteristic of Haydn's late style. In the final chapter, the intention has been to illustrate some of the different functions of tonal contrast that grew up alongside and after those described in terms of Haydn's music. A contrast is drawn between Haydn's use of flattened submediant areas within a single key area, and the use by Mozart and Beethoven of similar effects for the purposes of modulating from first to second group key. Finally, some of the great first movements of Schubert are discussed to illustrate the growth of the principle of harmonic and expressive contrasts to encompass very large areas of tonal stability.